A node-based version of the cellular Potts model. (1st September 2016) - Scianna, Marco; Preziosi, Luigi
Abstract: The cellular Potts model (CPM) is a lattice-based Monte Carlo method that uses an energetic formalism to describe the phenomenological mechanisms underlying the biophysical problem of interest. We here propose a CPM-derived framework that relies on a node-based representation of cell-scale elements. This feature has relevant consequences on the overall simulation environment. First, our model can be implemented on any given domain, provided a proper discretization (which can be regular or irregular, fixed or time evolving). Then, it allowed an explicit representation of cell membranes, whose displacements realistically result in cell movement. Finally, our node-based approach can be easily interfaced with continuous mechanics or fluid dynamics models. The proposed computational environment is here applied to some simple biological phenomena, such as cell sorting and chemotactic migration, also in order to achieve an analysis of the performance of the underlying algorithm. This work is finally equipped with a critical comparison between the advantages and disadvantages of our model with respect to the traditional CPM and to some similar vertex-based approaches. Abstract : Highlights: A node-based representation of the Cellular Potts Model is presented. Simulations of single cell and multicellular phenomena are proposed. An analysis of the computational efficiency of the model is performed. Advantages and disadvantages of the method are debated. A comparative discussion with similar approaches is included.